Implementasi Media Pembelajaran Video Tutorial Pada Kompetensi Rias Wajah Cikatri Pada Siswa Kelas XI Di SMK Negeri 3 Kediri - Hastagina, Mada Kartikaningdyah; Maspiyah; Sri Dwiyanti; Novia Restu Windayani (Program Studi Pendidikan Tata Rias, 2025)
The current education of cicatricial makeup competency does not use supporting learning media. This causes low student interest in following the learning process. The purpose of this study was to evaluate the effectiveness of using video tutorials, as well as to measure student learning outcomes and their reactions to the use of video tutorials in makeup skills in class XI of SMK Negeri 3 Kediri City. Quantitative methods were used, using a one-time case study. 36 students of class XI who studied skin and hair beauty were the subjects of the study. The results of the media expert validation recorded a score of 92%, while the validation by the linguist reached 90%, indicating that both were very feasible. The calculation of the average value in the student cognitive test was 95, where all students had achieved the Minimum Completion Criteria (≥80). Student responses were scored 4.8, indicating very good quality. The results of this study indicate that video tutorials are a very feasible and effective learning medium that improves student learning outcomes and has a very positive response from students. Keywords: video tutorial, competence, cikatri makeup.